THE EFFECTIVENESS OF USING PIXTON.COM IN WRITING STORYBOARD OF JUNIOR HIGH SCHOOL - Isti Chomah; Tatik Irawati (LPPM Universitas PGRI Jombang, 2024)
This study explores the effectiveness of Pixton.com in improving English writing skills among eighth-grade students. Using a quasi-experimental design, the research compares an experimental group that used Pixton.com with a control group that used conventional teaching methods. The focus was on students' ability to write storyboards about daily routines. The study involved two classes of eighth-grade students at MTs UW, selected based on teacher recommendations, with data collected through pre-test and post-test assessments. The results, analyzed using SPSS 25, revealed that the experimental group outperformed the control group, demonstrating a significant improvement in writing skills. The ANCOVA test further confirmed this significant difference, showing that Pixton.com had a positive impact on students' writing performance. The study also found that Pixton.com increased students’ motivation, creativity, and engagement in the writing process. Based on these findings, the study concludes that Pixton.com is an effective digital tool for enhancing students’ writing abilities and fostering a more interactive and engaging learning environment. Recommendations for English teachers include incorporating Pixton.com in writing lessons to improve language proficiency. Further research is suggested to investigate its broader applications in other educational contexts.